Synthesis and crystal structures of decahydro-closo-decaborates of the divalent cations of strontium and manganese - Jorgensen, Mathias; Lee, Young-Su; Paskevicius, Mark; Hansen, Bjarne R. S.; Jensen, Torben R. (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2021)
Efficient development of new solid-state electrolytes based on closo-boraces, an emerging class of ion conductors, relies on a thorough understanding of these materials, including their crystal structures and derived trends thereof. Here we present the syntheses and crystal structures of the first anhydrous decahydro-closo-decaborates of divalent cations (Sr2+ and Mn2+), expanding the library of available closo-borate compounds. The structures of the two compounds are highly dissimilar, displaying a distorted bcc- or helical anion sublattice, as well as a tetrahedral or trigonal coordination environment of the cation in SrB10H10 and MnB10H10, respectively. Crystal structures of two hydrates of the compounds were also solved, SrB10H10 center dot 4H(2)O and MnB10H10 center dot 6H(2)O, and the (di) hydrogen bond network was investigated based on their structures optimized by density functional theory. The characterization of these new compounds, as well as the insight provided by comparing with previously reported closo-boraces, are useful for designing new materials with high ionic conductivity or other desirable properties by revealing which compounds are likely to have compatible crystal structures, e.g. for aliovalent substitution.
Keywords: METALS; DODECABORATE; STABILITY; BORANES